Parafoveal-on-foveal effects are not an artifact of mislocated saccades - Allan Kennedy (Bern Open Publishing, 2008)
Oculomotor error leads to a proportion of saccades during reading missing the intended target. In this paper two kinds of mislocation are identified: either a word is erroneously refixated, or a word that was about to skipped is erroneously fixated. In both cases recorded fixation duration could be influenced by the fact that the overt fixation reflects neither the reader's intentions, not the current locus of attention. It has been argued that mislocations of this kind account for apparent "parafoveal-on-foveal" interactions and that, consequently, the challenge posed by such effects for serial processing models of eye movement control is more apparent than real. It is argued here that this analysis is flawed: mislocated fixations cannot plausibly act within the architecture of a serial model to produce effects mimicking parafoveal-on-foveal cross-talk. The claim that parafoveal-on-foveal effects are restricted to measurements made when the eyes are very close to the relevant parafoveal target is not supported in an analysis of the effects of cumulative lexical frequency on foveal processing time.